Size Categorization of Health Centers in Surin, 2007 - Pokpermdee, Pongsadhorn; Suktonaeng, Wimolwan; Sumalu, Jaruwan (Journal of Health Science of Thailand, 2018)
In Thailand, the health centers are the point of first contact to the health system for most patients. They provide integrated health care services for the people and plays an important role in Thai health care system. However, health centers are diverse in terms of service provided, catchment populations, number of patient visits, and number of staff. The varying sizes of health centers therefore require differing resource provision. Size categorization of health centers is one method to allow improved efficiency of resource allocation in health systems. The objective of this study is to develop the optimal method to categorize the size of health centers. Two methods were used in this study- a ranking score and an econometric model method. The econometric model was developed using the number of patient visits as a dependent variable to identify the factors that mostly influence the size of health centers. The explanatory variables are catchment population, number of village, number of staff, dentist care and health care provision by physician. The 2006 secondary data of health centers in Surin province was used in this study. The results indicate that the committee consensus method was not as optimal as the econometric model developed. Based on the latter model, health centers had been classified into 4 groups. The factors that showing impact on the size range of health centers included the catchment population, number of villages, staff size and availability of dental services. Collaborative participation from the staffs of health centers, academia and senior managers in the model development process was noteworthy. The limitations of the study are the invalid of some database and the time consuming process of collaboration with stakeholders. The model developed is recommended as a method to categorize the size range of health centers and improve the efficiency of resource allocation. Other factors such as provincial deprivation and health centers in border areas may be useful for inclusion in future models.